The Pharmacogenetics of Metformin: A Narrative Literature Review - Joneri, Alrahman (HM Publisher, 2021)
Metformin is one of the used medications for the treatment of type 2 diabetes. It works by reducing glucose production in the liver and improving glucose uptake and utilization in peripheral tissues. the pharmacogenetics of metformin is a rapidly evolving field with potential implications for personalized medicine. This review aimed is to explore the pharmacogenetics of metformin, including the genetic variants that may influence its efficacy and safety, as well as the potential implications for clinical practice. Genetic testing may be useful in identifying patients who are likely to benefit from metformin and those who are at higher risk for adverse effects. However, the implementation of genetic testing for metformin response in clinical practice faces several challenges, including cost, interpretation of test results, and the need for further evidence of clinical utility. In conclusion, the pharmacogenetics of metformin is a rapidly evolving field with potential implications for personalized medicine.